Integrating Resource-Based View and Social Innovation for Organizational Transformation: Evidence from a Leading Indonesian Water Utility Company - Dian Handayani; Rachma Fitriati (Majapahit Journal of Islamic Finance and Management, 2026)
This study investigates the transformation strategy of Perusahaan Umum Daerah. This study examines the transformation strategy of PERUMDAM Tirta Kerta Raharja (TKR) in Tangerang Regency to enhance drinking water service performance through the lens of the Resource-Based View (RBV) and social innovation. In 2024, the utility achieved a service coverage of 69.34 percent, surpassing its 60 percent target, despite persistent challenges such as limited raw water, a 15.60 percent water loss rate, and unchanged tariffs since 2009. Employing a qualitative document analysis of business plans and performance reports, the research identifies strategically valuable internal resources: water utilization permits (5,640 liters/second), SPAM infrastructure (6,267.5 liters/second across six zones), comprehensive demand data, BUMD legitimacy, and robust collaborative capacity. These resources are configured through production expansion, water-loss reduction, and idle-capacity optimization. Four key social innovations are identified: multi-stakeholder collaboration (e.g., SPAM asset grants from developers), hybrid public funding (APBN/APBD), community-needs approaches via surveys, and service digitalization (SCADA). The integration of RBV strategies and social innovation underpins performance gains, though profitability pressures and water-source vulnerability persist. This research contributes to public sector strategic management theory and offers practical insights for regional water utilities pursuing sustainable transformation.